2013
DOI: 10.1371/journal.pone.0059284
|View full text |Cite
|
Sign up to set email alerts
|

Clicking in Shallow Rivers: Short-Range Echolocation of Irrawaddy and Ganges River Dolphins in a Shallow, Acoustically Complex Habitat

Abstract: Toothed whales (Cetacea, odontoceti) use biosonar to navigate their environment and to find and catch prey. All studied toothed whale species have evolved highly directional, high-amplitude ultrasonic clicks suited for long-range echolocation of prey in open water. Little is known about the biosonar signals of toothed whale species inhabiting freshwater habitats such as endangered river dolphins. To address the evolutionary pressures shaping the echolocation signal parameters of non-marine toothed whales, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 69 publications
4
72
2
Order By: Relevance
“…Ranging calibration of the array was done in Aarhus Harbour, Denmark, from distances of 10 to 60 m with an HS70 hydrophone (Sonar Research and Development Ltd, Beverly, UK) acting as a transducer playing out two cycle pulses at 80 kHz as specified by a connected waveform generator (model 33220A, Agilent Technologies, CA, USA). The localisation calibration of the hydrophone array yielded a resulting error of less than 2 dB for the transmission loss estimate out to a range of 40 m, which is in line with accepted localisation errors in previous studies (Kyhn et al, 2009;Jensen et al, 2013).…”
Section: Acoustic Localisationsupporting
confidence: 88%
See 1 more Smart Citation
“…Ranging calibration of the array was done in Aarhus Harbour, Denmark, from distances of 10 to 60 m with an HS70 hydrophone (Sonar Research and Development Ltd, Beverly, UK) acting as a transducer playing out two cycle pulses at 80 kHz as specified by a connected waveform generator (model 33220A, Agilent Technologies, CA, USA). The localisation calibration of the hydrophone array yielded a resulting error of less than 2 dB for the transmission loss estimate out to a range of 40 m, which is in line with accepted localisation errors in previous studies (Kyhn et al, 2009;Jensen et al, 2013).…”
Section: Acoustic Localisationsupporting
confidence: 88%
“…Note that the baiji click is from a data set, where this click had one of the lowest peak frequencies, suggesting a potential underrepresentation of high-frequency energy in the power spectrum shown compared with the mean for this species. Ganges river dolphin data: Jensen et al, 2013;baiji data: Akamatsu et al, 1998;boto data: present program (LabView, Metrotech, Denmark). Recordings were saved onto the hard drive of a laptop in WAVE file format with continuous recordings being divided into files of 30 s duration.…”
Section: Recording Arraymentioning
confidence: 99%
“…Even though echolocation behaviour on a broader scale is comparable across species, the habitat and prey niche may be defining factors for the ICI step change that toothed whales use during the phases of target approach and buzzing and in the transition between the two Johnson et al, 2008;Madsen and Surlykke, 2013). Interestingly, we observed that botos, which in general click much faster than similarly sized marine toothed whales (Ladegaard et al, 2015), at rates comparable to other river-dwelling species (Jensen et al, 2013), decreased their ICIs from approach to buzzing only gradually from roughly 30 to 10 ms (Figs 2 and 3). In contrast, similarly sized marine species may downregulate ICI by more than an order of magnitude, ending with buzz ICIs as short as ∼2 ms when catching prey (DeRuiter et al, 2009;Wisniewska et al, 2014).…”
Section: Biosonar Behaviour Of Botos During Prey Interceptionmentioning
confidence: 61%
“…For example, an increasing number of studies have reported that many smaller toothed whales employ a form of gain control in the sense that they reduce their output levels during the approach phase to the target in a manner generally described as a 20log(R) relationship for decreasing target range, R (Au and BenoitBird, 2003;Jensen et al, 2009). However, some studies report a substantial deviation from that general trend while other data show no relationship between SL and range (Jensen et al, 2013), thus apparently suggesting no gain control at all. Such variation in gaze changes across species and studies as toothed whales approach a potential target begs the fundamental question of whether the studied animals did not adjust their biosonars during the approach phase or whether the researchers failed to identify the target that the animals were interested in and to which they therefore adjusted their acoustic gaze.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency with maximum intensity percentage clicks sound show in ( Figure 5). Click sound power have range 80-100 kU with -3 dB according in [23][24][25]. Frequencies with maximum intensity percentage click sound can be seen in (Figure 6).…”
Section: Characteristics Of Dolphin Soundsmentioning
confidence: 99%